GRAMMAR OF LANGUAGE OF GRAPHICAL VISUALIZATION OF MEDICAL DATA IMPLEMENTED IN PACKAGE GGPLOT2 - Martsenyuk, V. P.; Andrushchak, I. Ye.; Banadyha, A. I. (Medical Informatics and Engineering, 2017)
Application of package ggplot2 graphics grammar paradigm is shown on the example of medical researches data visualization. This approach offers a flexible instrument for the construction of multi-layered and multipanel charts on the basis of clinical and laboratory researches data.